Limitations of nasal nitric oxide measurement for diagnosis of primary ciliary dyskinesia with normal ultrastructure - Raidt, Johanna Felicitas; Krenz, Henrike; Tebbe, Johannes; Grosse-Onnebrink, Joerg; Olbrich, Heike; Loges, Niki Tomas; Biebach, Luisa; Schmalstieg, Christian; Kessler, Christina; Wallmeier, Julia; Dworniczak, Bernd; Pennekamp, Petra; et al. (Annals of the American Thoracic Society, 2022)
Rationale: Primary ciliary dyskinesia (PCD) is a heterogeneous, multisystem disorder characterized by defective ciliary beating. Diagnostic guidelines of the American Thoracic Society and European Respiratory Society recommend measurement of nasal nitric oxide (nNO) for PCD diagnosis. Several studies demonstrated low nNO production rates in PCD individuals, but underlying causes remain elusive. Objectives: To determine nNO production rates in a well-characterized PCD cohort, including subgroup analyses with regard to ultrastructural and ciliary beating phenotypes. Methods: This study included 301 individuals assessed according to European Respiratory Society guidelines. Diagnostic cutoffs for nNO production rates for this study cohort and subgroups with normal and abnormal ultrastructure were determined. Diagnostic accuracy was also tested for the widely used 77 nl/min cutoff in this study cohort. The relationship between nNO production rates and ciliary beat frequencies (CBFs) was evaluated. Results: The study cohort comprised 180 individuals with definite PCD diagnosis, including 160 individuals with genetic diagnosis, 16 individuals with probable PCD diagnosis, and 105 disease controls. The 77 nl/min nNO cutoff showed a test sensitivity of 0.92 and specificity of 0.86. Test sensitivity was lower (0.85) in the subgroup of 47 PCD individuals with normal ultrastructure compared with 133 PCD individuals with abnormal ultrastructure (0.95). The optimal diagnostic cutoff for the nNO production rate for the whole study cohort was 69.8 nl/min (sensitivity, 0.92; specificity, 0.89); however, it was 107.8 nl/min (sensitivity, 0.89; specificity, 0.78) for the subgroup of PCD with normal ultrastructure. PCD individuals with normal ultrastructure compared with abnormal ultrastructure showed higher ciliary motility. Consistently, PCD individuals with higher CBFs showed higher nNO production rates. In addition, laterality defects occurred less frequently in PCD with normal ultrastructure. Conclusions: Measurements of nNO below the widely used 77 nl/min cutoff are less sensitive in detecting PCD individuals with normal ultrastructure. Our findings indicate that higher nNO production in this subgroup with a higher cutoff for the nNO production rate (107.8 nl/min) and higher residual ciliary motility is dependent on the underlying molecular PCD defect. Higher nNO production rates, higher residual CBFs, and the lower prevalence of laterality defects hamper diagnosis of PCD with normal ultrastructure. Adjusting the cutoff of nNO production rate to 107.8 nl/min might promote diagnosing PCD with normal ultrastructure.